Innovative Strategies for Developing the Arabic Language Debate Community at University - Mokhamad Azis Aji Abdilah (Presscience, 2025)
Speaking skill, or mahārah al-kalām, is a skill that requires more than just linguistic proficiency; it also requires a certain setting and amount of practice. In addition to directly enhancing students' Arabic speaking abilities, the debate technique can unintentionally foster a language environment that has a significant impact on foreign language learners. The purpose of this study is to evaluate how well the debate approach works for enhancing Arabic speaking abilities. This study uses a descriptive qualitative approach and is conducted in the field. The note-taking method is the data collection methodology, and the intralingual equivalent method is used to evaluate the collected data. Overall proficiency in speaking Arabic has increased significantly by 61.5% as a result of this study. There was an 84% rise in the pronunciation component when speaking skills were taken into consideration. The percentage improvement was 87% in the vocabulary area. The percentage rise in PBA students' debate in the comprehension area was 75%, the percentage improvement in the fluency area was 82%, and the percentage gain in grammar accuracy was 74%. Pronunciation and fluency had the greatest average scores across the five categories in the PBA student debate community's post-test evaluation.